Features of pricing in construction and estimated cost of construction objects - Trunkina, L.V.; Syzdykova, E.Zh.; Shakeyev, S.S.; Shakenova, G.A. (BUKETOV BUSINESS REVIEW, 2019)
Capital construction involves a number of strategic important aspects, such as engineering, materials science, energetics, transport, etc. In this regard, the development and renewal of the construction process is an important step in the country’s overall development and economy. Pricing in construction is based on general principles, but also bears a number of specific aspects due to the characteristics of the industry and its products. The use of various methods can reduce the cost of construction and installation works. The price in construction is a monetary expression of the unit cost of construction products and is determined by the amount of socially necessary labor spent on its creation. The pricing mechanism in construction has specific features. First of all, this is due to the individual nature of the buildings and structures under construction, especially manifested in hydraulic engineering, a significant dependence of the cost of specific, often non-repeating conditions of construction. Such circumstances do not allow to establish uniform selling prices for construction products, as it is done in other sectors of the economy. Therefore, the price of construction products in the vast majority of cases is determined on an individual basis, on the basis of estimates in accordance with the scope of work, methods of production technology and a single register for certain types of work. A special pricing system has been developed to assess the cost of construction products. The analysis of existing estimated standards allows to draw a conclusion that there is a problem of discrepancy of estimated and market cost of construction. In this way, the research allowing to analyze the current estimated standards from different positions, to identify the positive and negative parameters, as well as to offer a solution to the identified inconsistencies becomes relevant.